Mesoscopic Modeling of a LiFePO4 Electrode: Experimental Validation under Continuous and Intermittent Operating Conditions. Issue 11 (1st January 2017) - Farkhondeh, M.; Pritzker, M.; Fowler, M.; Delacourt, C.
Abstract : The previously presented mesoscopic model [ Phys. Chem. Chem. Phys., 16, 22555, (2014)] for battery electrodes consisting of phase-change insertion materials is incorporated into porous-electrode theory and validated by comparing the simulation results with experimental data from continuous and intermittent galvanostatic discharge of a LiFePO4 electrode under various operating conditions. The model features mesoscopic LiFePO4 units that undergo non-equilibrium lithiation/delithiation and fast solid-state diffusion. Good agreement with the experimental data supports the validity of this model. GITT analysis suggests that the slow evolution of the electrode polarization during each pulse and the subsequent relaxation period is due to Li transport between LiFePO4 units rather than diffusion within the units. Galvanostatic pulse techniques commonly used to determine diffusivities of inserted species in solid-solution systems may also be used to estimate the equilibrium potential of individual mesoscopic units for which no actual measurement has been reported to date. Further analysis of the GITT experiments suggests an alternative pathway for the intermittent charge/discharge of LFP electrodes. Depending on the overall depth-of-discharge/charge of the electrode, relaxation time and the incremental depth-of-discharge/charge of each pulse, the solid-solution capacity available in the Li-rich/Li-poor end-member may be able to accommodate Li insertion/extraction entirely without phase transformation during each pulse.